1995
DOI: 10.1051/parasite/1995021063
|View full text |Cite
|
Sign up to set email alerts
|

Scanning electron microscope examination of scale-like spines on the rostellumm of five Davaineinae (Cestoda, Cyclophyllidea)

Abstract: S u m m a r y :The study by scanning electron microscope of the scolex of Davaineinae. ultrastucture. scanning electron microscopy, scale-like spines.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 0 publications
1
4
0
Order By: Relevance
“…The present work showed that C. polyacantha are characterized by square-shaped scolex with four unarmed circular suckers and large oval retractile rostellum armed with hooks arranged in 2 rows, behind these hooks, numerous very flat spines take scale-like shape forming indentation at the base of rostellum which in an agreement with the descriptions mentioned by Bâ et al (1995).…”
Section: Discussionsupporting
confidence: 92%
“…The present work showed that C. polyacantha are characterized by square-shaped scolex with four unarmed circular suckers and large oval retractile rostellum armed with hooks arranged in 2 rows, behind these hooks, numerous very flat spines take scale-like shape forming indentation at the base of rostellum which in an agreement with the descriptions mentioned by Bâ et al (1995).…”
Section: Discussionsupporting
confidence: 92%
“…25 The fine morphological structure of R. echinobothrida and related species is well understood. 26,27 In this study, we found that C. aroborea extract was evidently effective on the R. echinobothrida with dosedependent activity as that of albendazole. The antiparasitic activity was further substantiated by structural damages on the fine body surface.…”
Section: Discussionmentioning
confidence: 58%
“…23,24 The detail structural features of the tegument and its physical and physiological roles in poultry tapeworms are already amply described. 25,26 In our experiment, the methanol extract of I. khasiana leaves caused considerable tegumental damages including shrinkage, distortion of the spines and rostellum, and erosion of the microtriches. The antiparasitic activity was further substantiated by concentrationdependent lethal activity on R. tetragona similar to that of albendazole.…”
Section: Discussionmentioning
confidence: 62%